2006
DOI: 10.1007/s10934-006-9012-3
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum distribution in high-silica mordenite

Abstract: The Al distribution in high-silica MOR zeolites with various Si/Al ratios was investigated by FT-IR spectroscopy in the presence of CD 3 CN probe molecules and benzene adsorption. Two adsorption bands assigned to CN stretching vibration were observed at 2280-2295 and ≈ 2315 cm-1 , which are due to interaction of CN with acidic 1 hydroxyl groups in the main channels and the side pockets of H-MOR zeolite, respectively. The relative intensity of the peak at 2315 cm-1 increased with an increase in the Si/Al ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…As each unit cell of MOR contains 16 T 1 atoms, 16 T 2 atoms, 8 T 3 atoms and 8 T 4 atoms, the total number of Al atoms present at each T site scales as T 1 :T 2 :T 3 :T 4 = 36:20:43:29 the number of T 1 and T 2 sites is twice as large as the number of T 3 and T 4 sites). This result agrees well with quantum mechanical calculations that show the preferential occupancy of Al at the four-membered rings of MOR. This is also in agreement with results of molecular simulations. , …”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…As each unit cell of MOR contains 16 T 1 atoms, 16 T 2 atoms, 8 T 3 atoms and 8 T 4 atoms, the total number of Al atoms present at each T site scales as T 1 :T 2 :T 3 :T 4 = 36:20:43:29 the number of T 1 and T 2 sites is twice as large as the number of T 3 and T 4 sites). This result agrees well with quantum mechanical calculations that show the preferential occupancy of Al at the four-membered rings of MOR. This is also in agreement with results of molecular simulations. , …”
Section: Methodssupporting
confidence: 91%
“…For a more detailed description of the structure and symmetry of mordenite, we refer the reader to refs 39 and 40 The early study of Alberti et al 40 showed that in HMOR, the Al relative content of the T sites has a ratio of ). This result agrees well with quantum mechanical calculations [41][42][43][44] that show the preferential occupancy of Al at the four-membered rings of MOR. This is also in agreement with results of molecular simulations.…”
Section: Initial Location Of Framework Alsupporting
confidence: 91%
“…[85][86][87][88][89][90] The location of Al in the framework plays a vital role in determining the stabilization of exchanged cations, especially di or trivalent ions, and in turn the activity or stability of the catalyst. [91][92][93][94] Al distribution mainly depends on the Si/Al ratio, 95,96 and it controls not only activity but also hydrothermal stability. Yokoi et al 88 reported that the Al atoms located at the intersection of the ZSM-5 zeolite exhibited a shorter catalytic lifetime by investigating the correlation between the location of Al in the framework and catalytic activity/stability.…”
Section: Effect Of Al Distributionmentioning
confidence: 99%
“…The presence and concentration of aluminium sites in the zeolite framework can be assessed by many methods, e.g., elemental analysis. The issue of the local structure (the position of the [AlO 4 ] 5− units in the zeolite framework) has been, however, a matter of miscellaneous studies, both computational [17,[25][26][27] and experimental [25,[28][29][30][31][32][33][34][35], for decades. It is also known that the localisation of the Al sites is strongly dependent on the synthesis procedure and hard to reproduce [36,37].…”
Section: Localisation Of Aluminium Centres In Zeolite Structuresmentioning
confidence: 99%